The impact of motor vehicle emissions various traffic on the air the city of Ryazan in the spring - Tsurgan, Alexandr M.; Dementiev, Aleksey A.; Lyapkalo, Alexandr A.; Mazhaysky, Yury A. (Journal of the Belarusian State University. Ecology, 2020)
The article presents the results of daily and weekly monitoring of the length of traffic flows with speeds of 5–10 km/h (severe conditions) and emissions of vehicles on the streets and ring roads of Ryazan in the spring. The material of the study was cartographic data published in the public domain on the website www.yandex.ru. Studies have shown that the cartographic method can be used to assess the anthropogenic impact of vehicles on the atmospheric air of settlements. At the same time, the formation of heavy transport conditions leads to a significant increase in anthropogenic air pollution of the city by vehicle emissions, especially in the morning and evening «rush hours», respectively 8 and 18 hours, on the streets at the end, and on the district roads in the middle of the working week. A significant increase in emissions of pollutants by road was revealed, the maximum values of which on separate stretches in the morning and evening “peak hours” can reach 20 and 40 % of the average emission, respectively. The largest increase in vehicle emission components was observed in the streets of the city centre and in the morning and evening “peak hours” averaged 18.3 and 20.0 %, respectively.